Performance and JSE listing of selected South African hospital operators - Mokgatlhe, Kagiso Davis (Graduate School of Business (GSB), 2022)
The study investigates the relationship between the Johannesburg Stock Exchange Listing Status and performance of selected South African private Hospital Operators covering a 10- year period from 2008-2017. The selected proxies for the hospital performance measured were: Total Annual Revenue, Revenue per Bed per Day, Total Number of Hospital Beds, and EBITDA margin while controlling for Healthcare Inflation and Medically Insured Population, respectively. The specified regression equation was expanded to include simultaneous equations for the proxies of hospital performance. From this system of simultaneous equations, the study estimated the panel regression model using Seemingly Unrelated Regression (SUR). The findings showed that (1) JSE-listed Hospital Operators command higher Total Annual Revenues generated, superior Hospital Bed Numbers, and higher Revenue per Bed per Day compared to their unlisted peers, but their operating efficiency is not superior to that of their unlisted peers. In addition, the study found (2) a positive and statistically significant relationship between JSE Listing Status and Private Hospital Operator Performance for the performance proxies of Total Annual Revenue, Revenue per Bed per Day and Total Number of Hospital Beds, but a positive statistically insignificant relationship in respect of EBIDTA margin, the operating efficiency measure of performance; (3) a positive statistically significant relationship between Medically Insured Population and Private Hospital Operator Performance for the performance proxies of Total Annual Revenue, Revenue per Bed per Day, Total Number of Hospital Beds, but a positive statistically insignificant relationship in respect of the operating efficiency measure of performance; (4) a negative statistically insignificant relationship between Healthcare Inflation and Private Hospital Operator Performance for the performance proxies of Total Annual Revenue, Revenue per Bed per Day, Total Number of Hospital Beds, but a positive also statistically insignificant relationship in respect of the operating efficiency measure of performance. These results corroborate the theoretical predictions and are supported by previous studies. The study has important implications for public bourse listing as a strategic organisational consideration in terms of funding mobilisation for corporate performance and growth strategy. The sizeable macroeconomic contribution of the private hospital sector, and the importance of the medical insurance-private hospital performance nexus, behoves policy makers to ensure that the proposed universal health fund in South Africa must not totally crowd out the development of private health insurance.